The influence of system quality, information quality, and service quality on the net benefit of academic information systems with user satisfaction as an intervening variable - Ivana Melinda; Amelia Setiawan; Samuel Wirawan; Hamfri Djajadikerta (Journal of Intelligent Decision Support System (IDSS), 2023)
The increasing interest of young people to occupy tertiary institutions of education, the higher the level of competition that exists. Therefore, every tertiary institution is competing to improve the quality of education by developing Student Portal. This study aims to determine how the influence of system quality, information quality, and service quality on net benefits mediated by student portal user satisfaction. This research was conducted by collecting 59 primary data of respondents through a questionnaire. The analytical test tool used SmartPLS v.3.2.7 with the SEM (Structural Equation Modeling) analysis method. The results of this study indicate that the quality of information and service quality has an influence on student portal user satisfaction, user satisfaction has an influence on net benefits, while the effect of system quality on user satisfaction cannot be proven statistically. In this situation, system quality, information quality, and service quality have a weak effect on net benefits with user satisfaction as a mediating variable